2017
DOI: 10.1590/s1806-92902017000300003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the reproductive activity of male goats raised under tropical climate conditions

Abstract: -This study analyzed seasonal variations in the testes, the concentration of sex hormones, the parameters of fresh and thawed semen, and the sexual behavior of male Alpine goats from a temperate region in a tropical climate and possible interference with fertility. The maximum and minimum temperature and luminosity were recorded daily, while seminal, hormonal, and behavioral assessments were carried out every fortnight. The maximum and minimum temperature (°C) and luminosity (h) were recorded daily always at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The baseline LH obtained in this study is lower than 2.31±0.06 Miu/ml and 31.38 ± 37.75 Miu/ml reported in Nsuka(Okpe & Anya, 2017) and Abeokuta (Oloye et al, 2017) respectively, both studies were conducted in West African dwarf goats in southern, Nigeria. However, the baseline LH obtained in this study agrees with 0.36±0.17 Miu/ml found in Alpine goats in Brazil(Dias et al, 2017). The baseline TEST level in this study (3.92±6.39 ng/ml) is higher than 1.0±1.21 ng/ml (Oloye et al, 2017), 2.83±0.49 ng/ml reported by Dias et al (2017) and 2.97±0.03 ng/ml reported byOkpe & Anya (2017).…”
supporting
confidence: 90%
“…The baseline LH obtained in this study is lower than 2.31±0.06 Miu/ml and 31.38 ± 37.75 Miu/ml reported in Nsuka(Okpe & Anya, 2017) and Abeokuta (Oloye et al, 2017) respectively, both studies were conducted in West African dwarf goats in southern, Nigeria. However, the baseline LH obtained in this study agrees with 0.36±0.17 Miu/ml found in Alpine goats in Brazil(Dias et al, 2017). The baseline TEST level in this study (3.92±6.39 ng/ml) is higher than 1.0±1.21 ng/ml (Oloye et al, 2017), 2.83±0.49 ng/ml reported by Dias et al (2017) and 2.97±0.03 ng/ml reported byOkpe & Anya (2017).…”
supporting
confidence: 90%
“…Dias et al. (2017) declared the highest concentrations of T in summer and autumn. Moreover, Ait et al.…”
Section: Discussionmentioning
confidence: 99%
“…This activity can be actively involved in regulating the reproductive performance of the testis (Carreau et al, 2007). Dias et al (2017) declared the highest concentrations of T in summer and autumn. Moreover, Ait et al (2013) suggested that plasma T concentrations of Arab goats were significantly higher in autumn (6.15 ± 3.81 ng/ml) compared to spring season (0.90 ± 1.27 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…However, total acrosome damage was surprisingly lower ( p < 0.05) in samples collected in spring just after washing and after 3 h incubation in control media. This finding could be related to physiological or structural differences of sperm membranes during the non-breeding season [ 37 ], although age and season had no identifiable effect on the acrosome integrity after incubation in IVF media.…”
Section: Discussionmentioning
confidence: 99%